Century Naive units in the Russian view of the world (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In article language of culture is considered. The special attention is given the quasistandard. The semantic nature of units is studied. Their differential signs are revealed. A cognitive specific is described. Mechanisms of formation the quasistandard are investigated.
Keywords: language; culture; thinking; stereotype; the quasistandard; the prototype